2021
DOI: 10.1289/ehp9424
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Maternal Serum Perfluoroalkyl Substances Concentrations with Early Adolescent Bone Mineral Content and Density: The Health Outcomes and Measures of the Environment (HOME) Study

Abstract: Background: Per- and polyfluoroalkyl substances (PFAS) may impair bone accrual and strength via endocrine disruption and nuclear receptor agonism, but human studies are primarily of adults or cross-sectional. Objectives: We assessed associations of individual PFAS and their mixture during pregnancy with child bone mineral content (BMC) and areal bone mineral density (aBMD) at age 12 y. Methods: Among 206 mother–child pairs enrolled in a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 74 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…The authors found that higher concentrations of several PFAS and phthalate biomarkers were associated with lower total body less head aBMD Z scores in males, while there were modest positive associations with aBMD for some chemicals among females. Similar to prior epidemiologic studies examining prenatal ( 4 , 5 ) or childhood ( 6 , 7 ) PFAS exposures, Carwile and colleagues found the strongest magnitude of association for exposure to perfluorooctanoate.…”
mentioning
confidence: 57%
“…The authors found that higher concentrations of several PFAS and phthalate biomarkers were associated with lower total body less head aBMD Z scores in males, while there were modest positive associations with aBMD for some chemicals among females. Similar to prior epidemiologic studies examining prenatal ( 4 , 5 ) or childhood ( 6 , 7 ) PFAS exposures, Carwile and colleagues found the strongest magnitude of association for exposure to perfluorooctanoate.…”
mentioning
confidence: 57%
“…Also in a prospective study, PFOA and PFOS were associated with low BMD at several sites including spine, total hip, femoral neck, and hip rotor, and similar correlations were found for PFHxS, PFNA, and perfluorodecanoic acid (PFDA) in the intertransverse region of the hip ( 32 ). In addition to reports examining the relationship between a specific population’s autologous PFAS exposure and bone mineral density, several studies have found a negative correlation between serum PFAS concentrations in women exposed prenatally to PFAS and their offspring’s site-specific bone mineral density ( 14 , 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the use PFASs is now widely restricted ( ), a significant percentage of the global population is still exposed to them. PFAS have been classified as endocrine-disrupting chemicals (EDCs) ( 9 ), which together with other EDCs have been shown to be strongly associated with a wide range of human health issues including male and female reproductive health, obesity and metabolism, neurodevelopment, and bone health ( 10 , 11 ), however, few studies have reported on the effects of such environmental pollutant exposures on adolescent bone health ( 12 , 13 ), and previous studies on PFAS exposure in adolescent bone health have only primarily collected maternal prenatal PFAS exposure levels ( 14 , 15 ), therefore the extent of the effect of different PFAS on BMD in adolescents is unclear. However, on the basis of the limited available data suggesting a negative association between PFAS exposure and BMD, we proceeded to test the hypothesis that higher PFAS concentrations are associated with lower BMD in the NHANES 2005-2010 cross-sectional survey of adolescents aged 12-19 years.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Since they were widely measured in wildlife and the human body from the early 21 st century, the escalating contamination by PFAS has attracted sustained attention. [ 3 ] Exposure to PFAS through contaminated water has been linked to adverse health effects such as diabetes, [ 4 ] osteoporosis, [ 5 ] and miscarriage. [ 6 ] With restricted regulations aiming at anionic PFAS elimination, millions of dollars have been invested in handling these “forever chemicals”.…”
Section: Introductionmentioning
confidence: 99%